Factors Affecting Organizational Citizenship Behavior among Malaysian Bank Employees: The Moderating Role of Islamic Work Ethic. (15th June 2016) - Mohammad, Jihad; Quoquab, Farzana; Omar, Rosmini
Abstract: The inconsistent relationships between distributive justice, procedural justice and organizational citizenship behaviour have inspired this research to introduce a new moderator variable. This study includes Islamic work ethic as a third variable that has the potential to resolve conflict in the existing literature. To achieve the objectives of this study, data was collected through a survey of 192 employees at Islamic banks in Malaysia. The partial least square technique was employed to analyse the data. The results of this study revealed that distributive justice and procedural justice predicts organizational citizenship behaviour. The findings also suggested that Islamic work ethic predicts organizational citizenship behaviour. However, contrary to expectation, Islamic work ethic does not moderate the relationships between distributive justice, procedural justice and organizational citizenship behaviour. The limitations and suggestions for future research are discussed here.